1999
DOI: 10.1161/01.str.30.8.1671
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Mediates Astrocyte-Specific Regulation of Brain Endothelial Anticoagulant Factors

Abstract: Background and Purpose-Astrocytes are potent regulators of brain capillary endothelial cell function. Recently, astrocytes were shown to regulate brain capillary endothelial expression of the fibrinolytic enzyme tissue plasminogen activator (tPA) and the anticoagulant thrombomodulin (TM). To study the mechanism of this process, we examined the hypothesis that astrocyte regulation of endothelial tPA and TM is mediated by transforming growth factor-␤ (TGF-␤). Methods-Brain capillary endothelial cells were grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 75 publications
3
46
0
1
Order By: Relevance
“…Recent evidence has shown that MMPs are involved in the enzymatic digestion of the extracellular matrix (8,10,39). Interestingly serum levels of MMP-9 correlate with hemorrhagic conversion after thrombolytic therapy for acute stroke (40), suggesting that BBB damage may play a role in tissue plasminogen activator toxicity (41)(42)(43). The findings presented here demonstrate that, in addition to potentially deleterious molecular events, antiproteolytic molecules such as ␣ 2 M are also produced.…”
Section: Fig 2 Radial Immunodiffusion Analysis Demonstrating Increamentioning
confidence: 56%
“…Recent evidence has shown that MMPs are involved in the enzymatic digestion of the extracellular matrix (8,10,39). Interestingly serum levels of MMP-9 correlate with hemorrhagic conversion after thrombolytic therapy for acute stroke (40), suggesting that BBB damage may play a role in tissue plasminogen activator toxicity (41)(42)(43). The findings presented here demonstrate that, in addition to potentially deleterious molecular events, antiproteolytic molecules such as ␣ 2 M are also produced.…”
Section: Fig 2 Radial Immunodiffusion Analysis Demonstrating Increamentioning
confidence: 56%
“…ACM is known to contain a number of factors such as transforming growth factor-␤ (TGF-␤) (Tran et al, 1999), S100␤ (Eriksen and Druse, 2001), fibroblast growth factor-2 (Reuss and Unsicker, 2000), plasminogen activator inhibitor-1 (Kimura et al, 2000), and others. Among them, we examined possible involvement of TGF-␤ in ACM-induced HO-1 expression, because TGF-␤ has been shown to induce HO-1 expression in epithelial cells (Hill-Kapturczak et al, 2000).…”
Section: )mentioning
confidence: 99%
“…The endothelial BBB phenotype shares many similarities with differentiated intestinal epithelial cells, such as a high transcellular resistance and high levels of ␥-glutamyl transpeptidase activity and glucose transport. Known glial-derived soluble mediators that induce BBB-like properties include transforming growth factor-␤ (TGF-␤) (Tran et al, 1999), GDNF (Igarashi et al, 1999), and angiotensins (Kakinuma et al, 1998), as well as extracellular matrix components such as tenascin (Gutowski et al, 1999). Several other poorly characterized soluble factors have also been described that induce BBB-like properties in brain and noncerebral-derived endothelial cells, for example by inhibiting endothelin-1 expression (Federici et al, 1995).…”
Section: Intestinal Mucosa and Blood-brain Barrier Paradigmmentioning
confidence: 99%